Afterword. Issue 2 (1st September 2020) - Flores, Patrick D.
Abstract : Artist Pepe Dayaw's impetus is instructive in light of this volume's content. His practice deems cooking 'a process that occupies the immediate, the emergent and the local.' For him it is a practice that provides 'a meditative space for digesting and ruminating what is emerging.' With this sentiment of converging as a framework for performative experiments, his art projects are events that center on cooking and how they convene 'informal and oral settings' such as eating together or meeting other people for drinks and how these constitute 'potent spaces for generating particular kinds of knowledge.' In Dayaw's schema, hunger is one such kind of knowledge. In the issue, we read attentive gestures towards energies that tend to slip away in the 'normative commitments' of disciplines and ideologies, to include performance and gender that in the hands of less generous minds harden, even coarsen, into self-righteous advocacies or condense in echo chambers designated as areas of study.